A preliminary checklist of harvestmen (Arachnida: Opiliones) in Malaysia - Fatin-Elina Kamarulzaman; Dzulhelmi Muhammad Nasir; Nur-Syahirah Mamat; Faszly Rahim; Izfa Riza Hazmi (Pusat Sistematik Serangga, Universiti Kebangsaan Malaysia, 2017)
This is the first series on harvestmen species representing a total of 67 species from 25 genera and 9 families of harvestmen (Opiliones) from Malaysia compiled from available literatures between 1900s till date. In addition, the preliminary field survey identified six harvestmen species which are Dentobunus luteus, Gagrella longipalpis, Koyamaia curvipes, Marthana ferruginea, Zaleptus quadrimaculata and Hoplodino gapensis collected at Bukit Sawak, Langkawi Island (Kedah) and Hutan Lipur Lata Jarum (Pahang) which are considered as new locality record for this country. This information could serve as basic guideline and reference for future studies on harvestmen in Malaysia.